Child Maltreatment in Hanoi, Vietnam and Its Consequences - Hai Trung Nguyễn (Asian Social Work Journal, 2018)
Annually, number of child maltreatment has been increasing gradually. The consequences of child maltreatment and abuse seriously and directly impact child development both in physical and mental aspects and last in following years. Recently, researchers have paid more attention to studying child maltreatment in combination with community and neighborhood as a strong intervention to this issue. This paper aims to provide general information about child maltreatment in Hanoi and its consequences. Study shows that children in Hanoi Vietnam get involve in 4 types of maltreatment which are Minor abuse, Severe abuse, Very Severe abuse, Neglect. Being maltreated, it also causes many problems to child development. Thus, this study recomends some solutions to deal with those problems